Business Incubators - Drivers of Innovation in the Entrepreneurial Ecosystem - Sabin Murariu; Oana Pricopoaia; Nicoleta Cristache; Tiberius Iustinian Stanciu (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
Business incubators play a key role in developing and supporting the entrepreneurial system as they provide a nurturing environment for start-ups, providing important resources and mentoring needed to turn innovative ideas into successful businesses. By facilitating access to experienced management and funding networks, incubators facilitate the growth and development of early-stage entrepreneurs. A characteristic element of incubators is the provision of innovation support, which is fundamental for market competitiveness. Strat-ups can be helped to optimize their go-to-market strategy and shorten their time-to-market through acceleration programs in business incubators. Accelerator programs increase the chances of success of new businesses, contributing to the dynamism of the whole entrepreneurial ecosystem. By gaining a deeper understanding of how business incubators contribute to entrepreneurial success, more effective strategies can be formulated to support new businesses and foster a dynamic entrepreneurial ecosystem. The significant impact of business incubators on entrepreneurship enables the creation of a collaborative environment where ideas can be effectively tested and developed. Incubators are important drivers of economic development, providing not only financial and technical resources, but also strategic support through mentoring and networking, contributing to the consolidation of a robust and sustainable entrepreneurial system capable of generating value and continuous innovation. In the present research we analyze the impact of business incubators on the entrepreneurial system by reviewing the existing literature. We used the VOSviewer tool to map and visualize research networks and the relationships between key concepts. The VOSviewer provides a clear picture of the current research landscape, highlighting both well-covered areas and gaps that require further investigation.